uPATO - Collective measures - Silva, F. G. M.; Nguyen, Q. T.; Correia, A. F. P. P.; Clemente, F. M.; Lourenço Martins, F. M. (Ultimate Performance Analysis Tool (uPATO), 2019)
A collection of metrics is presented in this chapter. This collection is categorized as meso-level (subgroup) or team metrics, depending on the scope. Each metric includes a description of a possible interpretation of the metric, and the pseudocode to implement it. Each pseudocode describes the cases for which it can be used (unweighted graphs, unweighted digraphs, weighted graphs, or weighted digraphs). When the description simply contains graph (or graphs), without any other specifier, it means that the pseudocode is valid for any of the four types of graphs. The included interpretation considers that the connections between the players are the passes performed between them.